2011
DOI: 10.4253/wjge.v3.i5.95
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between endoscopic sclerotherapy and band ligation for hemostasis of acute variceal bleeding

Abstract: AIM:To compare band ligation (BL) with endoscopic sclerotherapy (SCL) in patients admitted to an emergency unit for esophageal variceal rupture. METHODS:A prospective, randomized, single-center study without crossover was conducted. After endoscopic diagnosis of esophageal variceal rupture, patients were randomized into groups for SCL or BL treatment. Sclerotherapy was performed by ethanolamine oleate intravascular injection both above and below the rupture point, with a maximum volume of 20 mL. For BL patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Variations in the technique or the sclerosant used have not been shown to influence the outcome of bleeding rates . In a recent study Luz et al . found that EST and EVL were equally efficient for the control of acute variceal bleeding and there were no differences in early rebleeding rates, complications or mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the technique or the sclerosant used have not been shown to influence the outcome of bleeding rates . In a recent study Luz et al . found that EST and EVL were equally efficient for the control of acute variceal bleeding and there were no differences in early rebleeding rates, complications or mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding from oesophageal or gastric varices typically results in a high death rate. For bleeding oesophageal or gastric varices, endoscopy-guided injection sclerotherapy or band ligation of the bleeding varices are the most appropriate immediate treatment procedures 24. However, the facilities and expertise for these procedures are not always available in many developing countries where schistosomiasis is endemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, our question was whether the results obtained in the RCT conducted by members of our group and their colleagues 8 would be reproducible outside the artificial environment created by RCTs. Thus, our objective was to investigate the following 3 outcomes in patients with Child-Pugh class C cirrhosis who underwent endoscopic injection of n-butyl-2-cyanoacrylate to treat esophageal variceal hemorrhage: (1) rate of failure to control bleeding (up to 5 days after the index bleeding), (2) rate of failure of secondary prophylaxis (from 6 days until 6 weeks after the index bleeding), and (3) complication and mortality rates.…”
Section: Introductionmentioning
confidence: 90%
“…Patients with Child-Pugh class C cirrhosis, or those with class B cirrhosis with active bleeding at the index endoscopy, are at high risk for treatment failure and have a poor prognosis 5 6 7 8 9 . In a previous randomized controlled trial (RCT), conducted by several investigators among our group (S. E. M., S. C., P. S., and F. M.-F.) and their colleagues 8 , 88 patients with esophageal variceal bleeding were treated with sclerotherapy or elastic band ligation (EBL). Patients with Child-Pugh class C cirrhosis had a 6-week mortality rate of 45.7 %, whereas no deaths occurred in the group of patients with Child-Pugh class A cirrhosis ( P < 0.001).…”
Section: Introductionmentioning
confidence: 99%